A atuação de organizações militares em ecossistemas de inovação: uma análise no contexto brasileiro - Pereira, Alonso Luiz (Universidade do Vale do Rio dos Sinos, 2022)
Innovation ecosystems are characterized by the joint action of actors, such as government, industry and academia, in order to generate flows of knowledge and value, with effects on scientific, technological development and innovation in regions. Innovation ecosystems are a promising field of study, especially regarding the articulations and contributions of their potential actors. This study analyzes how military organizations work in research and innovation projects and contribute to the formation of innovation ecosystems. The study is justified, considering that the concepts and approaches related to the theme are in evolution; that no academic studies were found addressing how the articulations of military organizations with other actors occur and that the research, considering its originality and differentiated approach, has the potential to contribute with theoretical and empirical results. Concepts on innovation ecosystems, studies on the relationship between the public sector and the private sector in innovation, empirical studies on three consolidated innovation ecosystems in terms of innovation, in which military organizations play a prominent role in generating innovation, form the theoretical basis of the research, value and contribution to economic and social development. As a research method, the case study strategy is adopted. The case of the Brazilian Army (EB) in innovation processes was investigated, considering three incorporated cases, the Management and Technological Innovation Agency (AGITEC), the Defense, Industry and Innovation Academy System (SisDIA de Inovação) and the Integrated Border Monitoring System (SISFRON). Data are collected through document analysis, interviews and observation and analyzed in terms of content. Preliminary analysis categories are considered based on the theoretical framework and the data collected indicated additional subcategories. The results indicate that the processes of knowledge generation aimed at scientific and technological innovation have guided processes of transformation of the EB; that the articulations between actors in innovation contribute to the formation of innovation ecosystems; and that the importance of the public sector in encouraging innovation transcends the creation of infrastructure for innovation and the regulatory apparatus. It is also highlighted, as results, that the performance of the public sector in encouraging innovation has favored the performance of actors, among them, military organizations; that the generation of value in shared activities enables organizational transformations; and that military organizations have the potential to contribute to the generation of value in the formation of innovation ecosystems with economic and social gains, as long as they transcend their primary missions and articulate with other actors in initiatives aimed at conducting scientific and technological innovation processes.
Keywords: Ecossistemas de inovação; Organizações militares; Conhecimento e inovação; Articulação entre atores; Geração de valor; Innovation ecosystems; Military organizations; Knowledge and innovation; Articulation between actors; Value generation; ACCNPQ::Ciências Sociais Aplicadas::Administração